Hydrogeochemical and isotopic analysis for interpreting the formation of the complex geothermal system in the Guide Basin, Northeastern Tibetan Plateau - Yude Lei; Zhen Zhao; Guangxiong Qin; Ruishou Ba; Shaokang Yang; Haoxin Shi (PLoS ONE, 2025)
The Guide Basin, located in the northeastern Tibetan Plateau, is rich in geothermal resources. However, whether the genesis of all geothermal waters in the basin is consistent remains an unresolved question. To clarify the geothermal system in this area, this study investigated the hydrogeochemical and isotopic characteristics of geothermal waters, combined with an analysis of the distribution and properties of regional faults. The study analyzed the processes controlling the chemical composition of thermal waters and the reservoir temperatures, ultimately creating a conceptual model of geothermal fluids. The results indicate that the geothermal waters in the Luohantang and Zhacanggou areas are classified as Na-SO4·Cl type, while those in the Xinjie area are classified as Na-HCO3 and Na-HCO3·Cl type. The chemical composition of geothermal waters is primarily controlled by the weathering of silicates, with some influence from carbonate dissolution and cation exchange processes. Isotope data (δD, δ18O, and 87Sr/86Sr) indicate that all geothermal waters originate from atmospheric precipitation and undergo deep circulation. The heat source in Guide Basin comes from mantle heat flow and granite radioactive decay, but the thermal storage patterns in the three regions of the basin are different. The use of cation and silica geothermometers estimates the reservoir temperatures in the basin to range between 82.4 °C and 229 °C. This study enhances the understanding of the genesis of geothermal resources in the northeastern Tibetan Plateau and provides important information for guiding future geothermal exploration in the area.